(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In the present work the optical properties have been investigated for the composite semiconductor material is Indium Nitrite (InN). In this study the multiphoton absorption phenomenon for the photon have been depended. The absorption spectrum for the Indium nitrite (InN) was recorded by using 5000 Varian UV-VIB-NIR Cary spectroscopy. The thickness of the thin film was calculated to be 3.5µm